Empowerment of Mediation as an Alternative Dispute Resolution for Divorce Cases in the Religious Court of West Nusa Tenggara - Haeratun (PT FORMOSA CENDEKIA GLOBAL, 2023)
The empowerment of mediation as an alternative solution to divorce cases in the Religious Court of West Nusa Tenggara is imperative to ensure that every case can be resolved amicably, following the parties’ agreement. Therefore, it is necessary to improve the certification training for non-certified mediator judges. This will enable them to acquire the requisite skills to reconcile parties in litigation and enhance the success rate of mediation. This study examines the Empowerment of Mediation as an Alternative Dispute Resolution to Divorce Cases in the Religious Court of West Nusa Tenggara as a principle to reduce the backlog of cases in the Religious Court, even up to the Cassation Level in the Supreme Court. It used primary legal sources from interviews with competent sources such as Mediator Judges in the Religious Courts, lawyers for the parties, and the parties involved in litigation. Meanwhile, relevant scientific literature, case studies, and expert opinions were used as secondary legal sources. The lack of legal awareness of the parties involved has also contributed to this problem, as many do not comply with existing legal rules. Furthermore, a contributing factor is the lack of infrastructure, such as the insufficient number of courts with adequate mediation rooms and equipment for remote audio-visual communication in courts